(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article provides a comprehensive examination of adverbs as a major part of speech in English grammar, focusing on their structural, semantic, and grammatical characteristics. The study begins by presenting the definition of adverbs and explaining their grammatical functions, including modification of verbs, adjectives, other adverbs, and entire clauses. The article describes the structural types of adverbs, such as simple adverbs, derived adverbs, compound adverbs, and phrasal adverbs, each defined and illustrated with examples. The discussion then expands to the semantic classification, explaining major meaning-based groups: adverbs of manner, time, place, frequency, degree, probability, focusing, and evaluative adverbs, each accompanied by a precise definition.